Physicochemical and microbiological analysis of dairy effluent - Mogha, Kanchan V; Prajapati, Jashbhai; Hati, Subrota (Indian Journal of Dairy Science, 2014)
Physicochemical and microbial analysis of dairy waste waters of 12 dairy plants was carried out. It was observed that pH of treated effluent samples varied from 6.7 to 8.1, while total dissolved solids (TDS) ranged from 650 to 2100 mg/lit. The chemical oxygen demand (COD) and Biological oxygen demand (BOD) of the effluent ready for disposal varied from 55-650 mg/lit and 20-150 mg/lit, respectively and the plate count was 5.62 and 5.61 log10 cfu/ml at 25 oC and 37 o C respectively. Microflora from treated effluents showed dominance of genus Bacillus followed by Alcaligenes, Pseudomonas, Citrobacter and Sporolactobacillus.